Analysis of the Individual Support Capacity of Pile Foundations Using a Pile Driving Analyzer Test Control Instrument: A Case Study of the SPK CSA Building Tower Plan 3A in Sidoarjo- Surabaya - Haza Fitra Anugrah; Nemesius Bambang Revantoro (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
Foundations play a crucial role in the stability of structures.  The 8-story CSA Tower SPK Building Plan 3A project uses pile foundations to support the load from the top of the structure to the soil layer beneath the building.  Pile foundations must undergo testing to demonstrate their ability to bear load.  This study analyzes the ultimate bearing capacity through a comparative analytical approach between the dynamic Pile Driving Analyzer Test (PDA) method and advanced analysis using CAPWAP (Case Pile Wave Analysis Program) with a numerical analysis method by evaluating the bearing capacity based on force and velocity wave data from the PDA Test to simulate static load tests and predict load displacement behavior.  The results of the study show that the maximum energy transfer (EMX) for the three different pile foundations, each with a pile number of T-174, is 5.60 tons.m, pile number T-317 of 4.37 ton.m, and pile number GT-31 of 5.60 ton.m, all tested with a Drop Hammer type weighing ±  4.00 tons at a height range of 1.5-2 m.  Further CAPWAP analysis results showed an average bearing capacity of 238.70 tons, which is 5.34% lower than the PDA result of 249.67 tons. The difference is due to more precise mathematical corrections in CAPWAP through signal matching analysis. Based on the maximum settlement standard of 25 mm, the maximum settlement in this study was 15.92 mm, with values below the maximum confirming the reliability of the foundation design. The PDA Test results showed the ultimate bearing capacity of the pile foundation.